2010
DOI: 10.2967/jnumed.110.077891
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking Macrophage Migration Using Reporter Gene Imaging with Human Sodium Iodide Symporter in Animal Models of Inflammation

Abstract: The aim of this study was to investigate the feasibility of nuclear molecular imaging using the human sodium iodide symporter (hNIS) as a reporter gene to monitor macrophage migration toward the inflammatory foci. Methods: A stable macrophage cell line coexpressing hNIS and green fluorescent protein (GFP) genes (RAW264.7/hNIS-GFP and R NIS cell) was established from an immortalized macrophage cell line (RAW264.7 cells). 125 I uptake was determined (for hNIS protein functional activity), and flow cytometry anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…NIS overexpression was also reported for several nonthyroidal cancer types including colorectal, lung, and a subset of breast cancers (13,(20)(21)(22)(23)(24), but it remains to be determined if those NIS expression levels are sufficient and consistent enough for accurate diagnosis and therapy. NIS has also been used as a reporter gene preclinically in cardiac (25), hematopoietic (26), and neural studies (27); for tracking macrophage migration (28); and for noninvasive imaging of gene therapy vectors (29,30). It has not yet been used for cancer metastasis tracking.…”
mentioning
confidence: 99%
“…NIS overexpression was also reported for several nonthyroidal cancer types including colorectal, lung, and a subset of breast cancers (13,(20)(21)(22)(23)(24), but it remains to be determined if those NIS expression levels are sufficient and consistent enough for accurate diagnosis and therapy. NIS has also been used as a reporter gene preclinically in cardiac (25), hematopoietic (26), and neural studies (27); for tracking macrophage migration (28); and for noninvasive imaging of gene therapy vectors (29,30). It has not yet been used for cancer metastasis tracking.…”
mentioning
confidence: 99%
“…3B). Although expression of sodium iodide symporter alone is sufficient to accumulate 99m Tc-pertechnetate in a cell (14,15), we found that incubation with Sn 2+ , which diffuses across the cell membrane, accumulates intracellularly, and reduces Tc 7+ , helped to retain the radioisotope.…”
Section: Resultsmentioning
confidence: 70%
“…After cells have been transfected with the symporter gene, using an adenovirus as the carrier, they can be imaged by injecting any of the isotopes of iodine or 99m Tc pertechnetate. This approach has been used recently to study the trafficking of macrophages in humans [79]. …”
Section: Cell Traffickingmentioning
confidence: 99%